Analyzing Epistemological Learning Obstacles on Limit Concept Using AVAE Framework in Prospective Mathematics Teacher - Ulfah Nur Azizah; Encum Sumiaty; Nadia Ulfa (Ar-Riyadhiyyat: Journal of Mathematics Education, 2025)
This study aims to identify the epistemological learning obstacles experienced by prospective mathematics teacher students in understanding the concept of limits in Calculus 1 lectures and the concept of limits. The primary focus of the analysis was conducted based on the categories of AVAE ERRORS (ARITH, VAR, AE, and EQS) related to the student's algebraic ability. The method employed was qualitative research involving 38 prospective mathematics teachers from one of the universities in West Java. Data was collected through written tests and confirmation interviews. The results showed that the most dominant epistemological learning obstacles were in the categories of AE (errors in algebraic expressions) and ARITH (arithmetic errors). These findings suggest that students struggle to apply prerequisite knowledge effectively to more complex limit problems. Therefore, a learning approach is needed that emphasizes not only algebraic procedures but also a deep conceptual understanding of the concept of limits.